Not only phosphorus: dauciform roots can also influence aboveground biomass through root morphological traits and metal cation concentrations - Huang, Yulin; Fan, Rong; Wang, Xiaoqi; Jiang, Songlin; Liu, Wanting; Ji, Wenli; Li, Weizhong (Frontiers in Plant Science, 2024)
Background Phosphorus in the soil is mostly too insoluble for plants to utilize, resulting in inhibited aboveground biomass, while Carex can maintain their aboveground biomass through the presence of dauciform roots. However, dauciform roots lead to both morphological and physiological changes in the root system, making their primary mechanism unclear.Methods A greenhouse experiment was conducted on three Carex species, in which Al-P, Ca-P, Fe-P, and K-P were employed as sole phosphorus sources. The plants were harvested and assessed after 30, 60 and 90 days. Results (1) The density of dauciform roots was positively correlated with root length and specific root length, positively influencing aboveground biomass at all three stages. (2) The aboveground phosphorus concentration showed a negative correlation with both dauciform root density and aboveground biomass in the first two stages, which became positive in the third stage. (3) Aboveground biomass correlated negatively with the aboveground Al concentration, and positively with Ca and Fe concentration (except Al-P). (4) Root morphological traits emerged as critical factors in dauciform root' promotion of aboveground biomass accumulation.Conclusions Despite the difference among insoluble phosphorus, dauciform roots have a contributing effect on aboveground growth status over time, mainly by regulating root morphological traits. This study contributes to our understanding of short-term variation in dauciform roots and their regulatory mechanisms that enhance Carex aboveground biomass under low available phosphorus conditions.